Craniofacial Morphology and Knowledge of the Stability in Class III Malocclusion Growing Subjects - Razza, F.C. De; Balboni, A.; Lugli, L.; Loberto, S.; Bollero, P. (International Journal of Pediatrics and Child Health, 2024)
Introduction: to investigate the palatal and craniofacial relationship in Class III growing patients between successful and failed treated groups. Methods: Thirty-one patients treated with RME/FM/BB were enrolled (inclusion criteria: Caucasian ancestry, III Class malocclusion, maturation stage CS1-CS2, mixed dentition). Digital cast and cephalometric analysis were performed on pre-treatment and post-treatment records. Statistical analysis and a discriminant analysis was performed. GMM was used on digital dental casts with Procrustes analysis to assess the covariation between palatal and craniofacial morphology. Two groups (relapse, R, 19 and success S, 12) were identified. Results: R group showed a greater maxillary-anterior transversal width at T0. At T1 R showed a shorter maxillary-anterior length than S. A larger maxillary-anterior and posterior-transversal widths was found in both groups. S had greater maxillary-anterior and posterior-sagittal length. A larger mandibular-anterior and posterior-transversal widths was shown in R, while S showed no differences in mandibula. Maxillary-anterior and maxillary-posterior length were two predictive variables found by discriminant analysis. The PC1 showed significant changes in the palatal morphology and revealed differences for the craniofacial vertical components. Palatal and craniofacial shapes showed a significant covariation, linking the palatal width to skeletal divergence. Discussion: In Class III malocclusion increases in vertical divergence are correlated with a higher palatal vault and narrower width. A wider and shorter maxillary morphology could be a relapse factor for Class III orthopedic treatment, while the lack of mandibular modification could be predisposing for treatment success.